Reduction of adverse effects from intravenous acetylcysteine treatment for paracetamol poisoning: a randomised controlled trial - Bateman, D Nicholas; Dear, James W; Thanacoody, H K Ruben; Thomas, Simon H L; Eddleston, Michael; Sandilands, Euan A; Coyle, Judy; Cooper, Jamie G; Rodriguez, Aryelly; Butcher, Isabella; Lewis, Steff C; Vliegenthart, A D Bastiaan; et al. (The Lancet (British edition), 2014)
Paracetamol poisoning is common worldwide. It is treated with intravenous acetylcysteine, but the standard regimen is complex and associated with frequent adverse effects related to concentration, which can cause treatment interruption. We aimed to ascertain whether adverse effects could be reduced with either a shorter modified acetylcysteine schedule, antiemetic pretreatment, or both. We undertook a double-blind, randomised factorial study at three UK hospitals, between Sept 6, 2010, and Dec 31, 2012. We randomly allocated patients with acute paracetamol overdose to either the standard intravenous acetylcysteine regimen (duration 20·25 h) or a shorter (12 h) modified protocol, with or without intravenous ondansetron pretreatment (4 mg). Masking was achieved by infusion of 5% dextrose (during acetylcysteine delivery) or saline (for antiemetic pretreatment). Randomisation was done via the internet and included a minimisation procedure by prognostic factors. The primary outcome was absence of vomiting, retching, or need for rescue antiemetic treatment at 2 h. Prespecified secondary outcomes included a greater than 50% increase in alanine aminotransferase activity over the admission value. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov (identifier NCT01050270). Of 222 patients who underwent randomisation, 217 were assessable 2 h after the start of acetylcysteine treatment. Vomiting, retching, or need for rescue antiemetic treatment at 2 h was reported in 39 of 108 patients assigned to the shorter modified protocol compared with 71 of 109 allocated to the standard acetylcysteine regimen (adjusted odds ratio 0·26, 97·5% CI 0·13–0·52; p<0·0001), and in 45 of 109 patients who received ondansetron compared with 65 of 108 allocated placebo (0·41, 0·20–0·80; p=0·003). Severe anaphylactoid reactions were recorded in five patients assigned to the shorter modified acetylcysteine regimen versus 31 who were allocated to the standard protocol (adjusted common odds ratio 0·23, 97·5% CI 0·12–0·43; p<0·0001). The proportion of patients with a 50% increase in alanine aminotransferase activity did not differ between the standard (13/101) and shorter modified (9/100) regimens (adjusted odds ratio 0·60, 97·5% CI 0·20–1·83); however, the proportion was higher with ondansetron (16/100) than with placebo (6/101; 3·30, 1·01–10·72; p=0·024). In patients with paracetamol poisoning, a 12 h modified acetylcysteine regimen resulted in less vomiting, fewer anaphylactoid reactions, and reduced need for treatment interruption. This study was not powered to detect non-inferiority of the shorter protocol versus the standard approach; therefore, further research is needed to confirm the efficacy of the 12 h modified acetylcysteine regimen. Chief Scientist Office of the Scottish Government.